Association between perfluoroalkyl substance exposure and thyroid hormone/thyroid antibody levels in maternal and cord blood: The Hokkaido Study. (December 2019) - Itoh, Sachiko; Araki, Atsuko; Miyashita, Chihiro; Yamazaki, Keiko; Goudarzi, Houman; Minatoya, Machiko; Ait Bamai, Yu; Kobayashi, Sumitaka; Okada, Emiko; Kashino, Ikuko; Yuasa, Motoyuki; Baba, Toshiaki; et al.
Abstract: Background: Thyroid antibodies (TAs) are the most common cause of hypothyroidism during gestation. Although previous studies found that prenatal exposure to perfluoroalkyl substances (PFASs) disrupts thyroid hormones (THs) in humans, their effects on TAs during the perinatal period have not been investigated. Objective: To explore the associations between prenatal exposure to eleven different PFASs from two different groups (carboxylates and sulfonates) and the expression of THs and TAs in maternal and cord blood while considering maternal TA status. Methods: In a prospective birth cohort (the Hokkaido Study), we included 701 mother‑neonate pairs recruited in 2002–2005 for whom both prenatal maternal and cord blood samples were available. Eleven PFASs were measured in maternal plasma obtained at 28–32 weeks of gestation using ultra-performance liquid chromatography coupled with triple quadrupole tandem mass spectrometry. THs and TAs including thyroid stimulating hormone (TSH), free triiodothyronine (FT3), free thyroxine (FT4), thyroid peroxidase antibody (TPOAb), and thyroglobulin antibody (TgAb) were measured in maternal blood during early pregnancy (median 11 gestational weeks), and in cord blood at birth. Results: The median levels of TgAb and TPOAb in maternal serum were 15.0 and 6.0 IU/mL, respectively. The median TgAb level in neonates was 38.0 IU/mL, and TPOAb were detected in only 12.3% of samples. Maternal FT3 level was positively associated with PFAS levels in both TA-positive and TA-negative mothers. Maternal perfluorooctanoate was inversely associated with maternal TPOAb. Among boys, some maternal PFASs were associated with higher TSH and lower FT3 levels in maternal TA-negative group, while perfluorodecanoic acid was associated with lower TSH in maternal TA-positive group. Among girls, some PFAS of mothers showed associations with lower TSH and higher FT3 in maternal TA-negative group, while perfluorododecanoic acid was associated with lower FT4 in maternal TA-positive. Maternal PFASs showed associations with boy's TgAb inversely in maternal TA-negative group and with girl's TgAb positively in maternal TA-positive group. Conclusions: Our results suggest thyroid disrupting effects of PFAS exposure and susceptibility vary depending on maternal TA levels. Highlights: We explored associations of maternal PFASs with TH and TA levels of mothers and neonates. This is the first study to examine effects of PFASs on TA levels in healthy neonates. Maternal PFAS levels were associated with maternal and neonatal THs and TAs. Current results indicate the sex difference on relationships between PFASs and neonatal thyroid status. Our results suggest the different susceptibility of neonatal TH and TA depending on maternal TA levels.